(untitled) (Biocenosis, 2013)
It presented the status of anurans of a zone of Pampa Argentina, considered representative of this region. The frogs are threatened with extinction worldwide and regionally, and its presence is crucial in the regulation of wetlands, so we analyze some causes of this decline. Is discussed especially habitat modification caused by the farm. We conclude that this situation is particularly serious in the region, and must be addressed properly to avoid a possible involvement of these animals. Also it should be deepened the morphological and histological analyzes or others to completely rule out the hypothesis of involvement of these animals by agrochemicals.